2014
DOI: 10.1111/jgs.12591
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Management in Individuals with Hip Fracture

Abstract: Active management in a GFC model to reverse anticoagulation before surgery may facilitate earlier surgery without increasing observed complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 30 publications
0
26
1
1
Order By: Relevance
“…The use of fresh-frozen plasma appears to be safe and significantly reduces time to surgical repair. 44,45 For patient taking newer anticoagulants like dabigatran, rivaroxaban and apixaban, there is no reversal therapy therefore, based on these products' package insert, a prudent time between the last dose of these medications and surgery is approximately 48 hours. This could be extended on patients with abnormal renal of hepatic function.…”
Section: Coagulopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of fresh-frozen plasma appears to be safe and significantly reduces time to surgical repair. 44,45 For patient taking newer anticoagulants like dabigatran, rivaroxaban and apixaban, there is no reversal therapy therefore, based on these products' package insert, a prudent time between the last dose of these medications and surgery is approximately 48 hours. This could be extended on patients with abnormal renal of hepatic function.…”
Section: Coagulopathiesmentioning
confidence: 99%
“…253,254 This system incorporates Codman 4 parts of the proximal humerus, namely, the anatomic head, the lesser tuberosity, greater tuberosity, and the humeral shaft ( Figure 10). 255 Displacement of more than 1 cm or angulation of the part by 45 or more allows the fragment to be counted as a part. Thus, a nondisplaced fracture would be zero parts and a fracture with displacement of greater than 1 cm of all 4 parts would be a 4-part fracture.…”
Section: Classificationmentioning
confidence: 99%
“…Recent studies have shown that early surgery in patients on clopidogrel and warfarin is safe with no increase in observed complications. [14][15][16] Removal of this delay would improve our time to surgery. Addition of a standardized pain management program and fracture prevention program may further improve our results.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the process of implementing warfarin reversal guidelines within hospital systems requires interdisciplinary collaboration between emergency room doctors, surgeons, medicine doctors, anesthesiologists, and nursing staff. In this context, the implementation of geriatric trauma centers seems to be a promising concept that may facilitate process improvements within this specific patient population [2,4].…”
Section: How Do We Get There?mentioning
confidence: 99%
“…Different approaches for warfarin reversal in patients with hip fracture have been suggested [1,2,[5][6][7][8]10]. Available options include prothrombin complex concentrate (PCC), fresh frozen plasma (FFP), and vitamin K [7].…”
mentioning
confidence: 99%